UTILIZATION OF ACTIVATED OF KEPOK BANANA PEEL POWDER (Musa paradisiaca L.) AS AN ADSORBENT OF CADMIUM METAL IONS (Cd2+) - Malik, Abdilla; -, Alimuddin; Gunawan, Rahmat (JURNAL ATOMIK, 2021)
Research on the adsorption of cadmium metal ions (Cd2+) using activated adsorbent from Kepok banana peel powder (Musa paradisiaca L.) has been carried out. Determination of the functional groups contained in the adsorbent used Fourier Transform Infrared Spectroscopy (FT-IR) instruments indicate the presence of O-H, C-O and N-H groups. Characterization of pores in the adsorbent using Scanning Electron Microscope (SEM) instruments that show the occurence of pore and cavity enlargement on the surface of the adsorbent, as well as the appearance of finer topography after the activation process. The result of this study indicate that the adsorbent of Kepok banana peel powder can absorb cadmium metal ions (Cd2+) with the best absorption occurs at optimum conditions pH 5, 60 minutes contact time and a concentration of 1.5 ppm. The adsorption capacity of the adsorbent of Kepok banana peel powder at the optimum conditions is 0.04991 mg/g.